Smart Farming: Mengintegrasikan Teknologi Pemantauan Nutrisi untuk Meningkatkan Kesejahteraan dan Produktivitas Hewan - Muhammad Raffin Althafullayya; Nila Puspita Aryani (Yayasan Perguruan Kampus, 2024)
The importance of integrating technology in farm to enhance efficiency, animal welfare, and operational sustainability. The research method employed is qualitative descriptive with a focus on literature review. The findings indicate that the concept of smart farming, involving process automation, sensor utilization and monitoring, and information system integration, can improve productivity and animal welfare. Nutrient monitoring technology, with nutrient sensors and integrated information systems, can ensure proper nutrient intake for livestock, enhancing their health and productivity. In conclusion, smart farming with nutrient monitoring technology brings significant benefits in supporting sustainable farm and improving animal welfare, while creating a positive environment for humans, animals, and the ecosystem.